The Development of Prosocial Behaviour in Infants: The Role of Participating with, Problem Solving for, and Requesting Help from Caregivers in the First Year of Life - Edwards, Victoria (Université d'Ottawa / University of Ottawa, 2023)
Babies and toddlers are known to help others in the second year of life, by doing simple things like picking up dropped toys. However, researchers now believe helping develops earlier, in the first year of life. After reviewing what is known about early helping, my thesis examined how babies begin to help others by first helping their mothers (Study 1), and, for the first time, babies' requests for help from others, and how their requests are related to their other helping experiences (Study 2). The two studies presented here look at how babies interact with their caregivers, naturalistically and in structured game-like activities, from the time that they are five months old until they are ten months old. Study 1 used video-chat with 40 babies and their mothers to see the connection between how mothers and their babies completed activities together naturalistically, and how babies performed in simple helping games, as well as how babies' helping in these activities changed over time. This study found that mothers used gestures and phrases with their babies that were like the ones used by researchers in experiments, that younger babies were more likely to help their moms in cooperation type activities than in problem solving type activities, and that babies were more likely to help in problem solving type activities when they were older. Study 2 looked at 34 different pairs of babies and mothers to identify how babies and their caregivers ask for help from each other. This study found that babies ask for help from their mothers and use similar types of communication as their mothers. This research gave information to help us understand babies' helping and how it develops through both mother-child interactions and babies' own actions. This research is new and gives exciting new information to other researchers that are interested in learning about how babies help others and how they ask for help from a very young age.
Keywords: Prosocial Behavior; Prosocial Behaviour; Infant Development; Infancy; Social Development; Parent-child Interaction; Helping; Instrumental Helping; Problem Solving; Participation; Moral Development